Clinical and epidemiological features of complex approaches in the treatment of osteoporosis in systemic scleroderma - Tuychiyev Sardor Azamatovich (Genius Journals, 2022)
Systemic sclerodermia is a disease of the connective tissue with an unknown etiology, clinical manifestations of heterogeneity and chronic progressive disease. It is based on 3 pathological processes: vasculopathy, cellular and humoral autoimmune conditions and progressive visceral and vascular fibrosis in many organs. In the United States alone, there are between 9 and 19 cases of disease per 1 million people. According to the National Osteoporosis Foundation (NOF), in the United States in 2010 more than 10 million adults age 50 years and older had osteoporosis and more than 43 million had low bone mineral density (BMD). In the United States in 2015, as many as 2 million Medicare beneficiaries sustained 2.3 million osteoporotic fractures. Within 12 months of experiencing a new osteoporotic fracture, approximately 15% of patients suffered one or more subsequent fractures and nearly 20% died. Mortality was highest in those with hip fracture, with 30% dying within 12 months
Keywords: Systemic scleroderma; diffuse systemic scleroderma; limited systemic scleroderma; gastric antral